Animal models of psychiatric disease. - Flint, J; Shifman, S (2008)
Animal models of psychiatric diseases are useful tools for screening new drugs and for investigating the mechanisms of those disorders. Despite the difficulties inherent in modelling human psychiatric phenotypes in animals, there has been recent success identifying mutations in mice that give rise to some of the characteristic features of anxiety, depression, schizophrenia, autism, obsessive-compulsive disorder and bipolar disorder. In some cases these models have the additional strength that drugs used to treat the human condition alleviate the symptoms in mice. Robust genetic evidence of the involvement of multiple susceptibility genes in psychiatric disease will enable future studies to move from single-gene models to models with multiple modified loci, with the promise of better representing the complexity of the human diseases.